Microwave Ablation of Hepatocellular Carcinoma and Liver Metastases: Challenges, Opportunities, and Future Directions - Stratchko, Lindsay M.; Koepsel, Erica M. Knavel; Ziemlewicz, Timothy J.; Knott, Emily A.; Hinshaw, J. Louis; Wells, Shane A.; Laeseke, Paul F.; Lee Jr, Fred T. (Digestive Disease Interventions, 2022)
Chronic liver disease predisposes patients to the development of hepatocellular carcinoma (HCC), and the degree of liver dysfunction helps dictate the management of patients with primary hepatic malignancy. Percutaneous ablation is an increasingly utilized treatment modality for patients with hepatocellular carcinoma who are poor surgical candidates, particularly when treatment goals include sparing hepatic parenchyma in the setting of hepatic dysfunction. Various thermal and non-thermal ablation modalities have historically been used to treat HCC. With advances in ablation technology, modern microwave (MW) ablation systems have become increasingly utilized in HCC as well as hepatic metastatic disease management due to larger and more predictable ablation zones. The evolution of ablation technology has resulted in the growth of ablation as a safe and effective treatment option for patients with primary and secondary liver tumors.
Keywords: hepatocellular carcinoma; hepatic metastases; microwave ablation